Assyrian Temple in the city of Guzana (Tell Halaf) - هادي علي فائز (Al-Adab Journal, 2018)
This search includes one Assyrian Temples constructed out of Assyria , which was constructed in accordance with the thought of the Assyrian known in the planning and building of Temples . This temple located in the Guzana city currently known as (Tell Halaf) and is an archaeological site large overlooking the Khabur river near the Ras Al-Ain village Syrian-Turkish border about (152 km) north-west of the city of Nineveh . The research also included a brief idea about the Guzana city history as well as the subject of the Assyrian empire wide during the first millennium BC. and based on the physical remnants discovered at the site and in particular architecture remains that has helped us in the study of the planning and building of the temple construction and the materials used in Guzana city built its construction conclude that temple according to the model of the Assyrian in the planning and building temples although there are many common characteristics between the Assyrian temples architecture and building temples in Mesopotamia.